Thin Partitions: Remembrance and Reflection in Alfred Fisher's Zakhor: Remember - Lewis, Christopher (Canadian University Music Review / Revue de musique des universités canadiennes, 1993)
The injunction to remember – in Hebrew, Zakhor – is perhaps the most powerful command in the Old Testament, and memory of the past has therefore always been a central component of Jewish experience. Alfred Fisher's character and music suggest both erudition and practicality as crucial components of the Jewish heritage that has formed an increasingly central part of his life and music during the past decade. In the song cycle Zakhor: Remember, poetic and musical cross-referencing of memories is the framework for a fascinating dialectic that informs the structure and the language of the cycle. In this article, the author studies the different levels of unity in the cycle and discusses its tonal structure, which can be characterized as post-Schoenbergian chromaticism, in which much of the harmonic language is controlled by a limited number of pitch-class sets. Remembrance and reflection are here interwoven with Fisher's emotional responses into the intellectual framework of a profound work of art.